Parental satisfaction with follow-up services for children with major anatomical congenital anomalies - Van Dijk, M.; Poley, M.; Gischler, S.; Mazer, P.; IJsselstijn, H.; Tibboel, D.; Latour, Jos (Blackwell Publishing Ltd, 2010)
Background: Since 1999 a multidisciplinary follow-up programme for parents and children with major anatomical congenital anomalies is in place in our hospital, run by a dedicated team. The aim of the present study was to evaluate the services of this team from a parental perspective. Methods: Parents completed a questionnaire including open and closed questions about satisfaction with the various professional disciplines involved in the follow-up, statements on usefulness of the follow-up services and suggestions for improvement. Results: Four hundred and sixty-nine surveys were sent out, of which 71% were returned. Non-responding parents included significantly more parents of non-Dutch origin (P = 0.038) and parents who never responded to invitations for follow-up examinations (P < 0.001). Parental satisfaction differed for the various disciplines. Eighty per cent of the parents were (very) satisfied with the social worker, compared with 92% with nurses. More than half of the parents agreed that the follow-up services give peace of mind. Almost a quarter of parents, however, considered the follow-up services as redundant. The children of these parents had significantly shorter intensive care unit stay (P = 0.02), were older at the time of the questionnaire (P = 0.04), of higher socio-economic status (P = 0.001) and less likely to be of non-Dutch origin (P = 0.008). Sixty-one per cent of the parents had contacted the 24-h helpline. Ninety per cent of the parents were satisfied with the intensive care unit, almost 80% with the general ward. Conclusion: Overall, parents were satisfied with the services of the follow-up team. Some parents, however, saw room for improvement related to better communication, recognizability of the team and better planning and organization. © 2009 The Authors. Journal compilation © 2009 Blackwell Publishing Ltd.